Construction of an ornidazole/bFGF-loaded electrospun composite membrane with a core-shell structure for guided tissue regeneration. (September 2022) - Zhang, Wen; Wang, Qianqian; Wang, Kairong; Ma, Hairong; Gong, Yuwei; Xu, Lihua; Zhang, Hualin
Graphical abstract: Highlights: The ornidazole (ONZ)/basic fibroblast growth factor (bFGF)-loaded composite membrane with a distinct core/shell structure was prepared by emulsion electrospinning. The early substantial release of ONZ and slow sustained release of bFGF were realized. The ONZ/bFGF-loaded composite membrane promoted in vivo periodontal tissue formation of periodontal tissue defects. The ONZ/bFGF-loaded composite membrane facilitated rapid wound healing of skin wound defects. Abstract: Postoperative infection caused by bacteria and limited amounts of regenerated tissue are important factors affecting the efficacy of guided tissue regeneration (GTR). However, a simple GTR membrane functions only as a mechanical barrier for isolation and lacks the ability to resist bacteria and actively induce tissue regeneration. In this study, an ornidazole (ONZ)/basic fibroblast growth factor (bFGF)-loaded poly(lactic- co -glycolic acid) (PLGA)/wool keratin (WK) composite membrane with a core/shell structure was prepared by emulsion electrospinning. ONZ was used in the shell layer to inhibit bacteria and bFGF in the core layer to accelerate tissue regeneration. The ONZ/bFGF composite membrane, with early substantial release of ONZ within 7 days and slow sustained release of bFGF for more than 28 days, exhibited good cell barrier function, cytocompatibility and degradability, and inhibited the proliferation of Pg, Fn and Pa over 21 days. Moreover, this composite membrane facilitated periodontal tissue regeneration and rapid wound healing. The ONZ/bFGF-loaded composite membrane is a strong candidate as a GTR membrane for periodontal tissue regeneration, and it also holds great potential as a functional dressing for skin defect repair. These results will broaden the prospects for the construction and application of multifunctional tissue engineering scaffolds for sustained drug release.